Cooling and Hypothermia Effect on Structural and Metabolic Characteristics of Bone (Review) - Poshelok, Denis M.; Dedukh, Ninel V.; Malyshkina, Svetlana V. (Problems of Cryobiology and Cryomedicine, 2014)
The review presents the basic concept of hypothermia and its classifications. The findings of hypothermia effect on cultured cells (osteoblasts and osteoclasts) as well as the effect of cold stress and different regimens of hypothermia on structural and metabolic characteristics of bone were analyzed. Probl Cryobiol Cryomed 2014; 24(4):279-291.